Pengaruh PDRB Perkapita dan Suku Bunga Riil terhadap Permintaan Kredit Konsumsi pada Bank Umum di Provinsi Bali - Komang Arip Jaya Kusuma; A. A. Sri Purnami; I Gede Aryawan (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2018)
The aims of this research is to find out how the influence of PDRB Per capita and the real interest rate partially and simultaneously on the demand for Consumer Loans at Commercial Banks in Bali Province. The analysis data technique is the classic assumption test, multiple linear regression analysis. The results of the research from the F test were obtained simultaneously by the PDRB Per capita and Real Interest Rate variables which significantly influenced the Consumer Credit at Commercial Banks in the Province of Bali. From the t test on the PDRB per capita variable has a positive and significant influence on the demand for Consumer Loans at Commercial Banks in the Province of Bali. From the t test on the Real Interest Rate variable has a negative and significant influence on the demand for Consumer Loans in Commercial Banks in the Province of Bali.